799 Durable responses and immune activation with intratumoral electroporation of pIL-12 plus pembrolizumab in actively progressing anti-PD-1 refractory advanced melanoma: KEYNOTE 695 interim data. (10th December 2020) - Fernandez-Penas, Pablo; Carlino, Matteo; Tsai, Katy; Atkinson, Victoria; Shaheen, Monaster; Thomas, Sajeve; Mihalcioiu, Catalin; Hagen, Tom Van; Roberts-Thomson, Rachel; Haydon, Andrew; Mant, Andrew; Butler, Marcus; et al.
Abstract : Background: Electroporated plasmid IL-12 (TAVO or tavokinogene telseplasmid) is a novel pro-inflammatory intratumoral therapy with substantial single agent activity in melanoma, which has been shown to synergize with anti-PD-1 antibodies in patients predicted as non-responders to anti-PD-1. 1 2 Interim data from patients with stage III/IV melanoma actively progressing on anti-PD-1 antibody are presented herein. Methods: Patients with confirmed disease progression by RECIST v1.1 after at least 12 weeks of treatment on pembrolizumab or nivolumab (or combination checkpoint blockade) and within 12 weeks of last dose (with no intervening therapies) were enrolled. There was no limit on the number of prior lines of therapy. At least one accessible lesion was electroporated with plasmid IL-12 (pIL-12-EP) on days 1, 5 and 8 every 6 weeks and pembrolizumab was administered every 3 weeks. Tumor response in treated and untreated lesions was assessed by RECIST v1.1 every 12 weeks. Endpoints include ORR, safety, PFS, OS, and DOR. Results: The first 56 patients treated of 100 planned were included in this interim analysis. Of these, 84% had Stage IV disease, 30% had M1c or M1d disease, and 27% had prior exposure to ipilimumab. In 54 efficacy evaluable patients the investigator-assessed ORR was 30% (3 CR/13 PR), 5 patients had 100% reduction of target lesions. All responses have been confirmed, only two responding patient progressed while on study, 2 patients completed the study with ongoing responses (figures 1 and 2 ). In patients with M1c/M1d disease, the ORR was 35.2% (n=6/17). Tumor reduction was observed in untreated lesions in 12 of 12 patients who had unaccessible lesions or accessible untreated lesions. The median overall survival (mOS) and duration of response (mDOR) has not been reached, with a median follow-up time of 13 months. Grade 3 treatment-related adverse events (TRAEs) were seen in 5.4% of patients, and there were no grade 4/5 TRAEs. The rate of grade 3 treatment-emergent (TEAEs) regardless of cause was 23.2%. The median time for pIL-12-EP treatment was 10 minutes (range 2, 46). Consistent with prior studies of single-agent pIL-12-EP, tumor IHC, and transcriptomic assessments revealed hallmarks of antigen-specific antitumor immunity in this study. Additional analyses including microbiome, TCR clonality, and peripheral blood biomarker assays will be presented. Conclusions: In this rigorously defined PD-1 antibody refractory patient population, the addition of pIL-12-EP to PD-1 antibody therapy induced deep, durable, systemic response in local treated and distant visceral metastatic untreated lesions with nominal systemic toxicity. Trial Registration: Trial Registration: NCT#03132675 Ethics Approval: The study was approved by a central IRB and/or local institutional IRBs/Ethics Committees as required for each participating institution. Consent: Written informed consent was obtained from the patients participating within the trial, the current abstract does not contain sensitive or identifiable information requiring an additional consent from patients. References: Algazi A, Bhatia S, Agarwala S, et al. Intratumoral delivery of tavokinogene telseplasmid yields systemic immune responses in metastatic melanoma patients. Annals of Oncology 2019;31 :532–540. Algazi A, Twitty C, Tsai K, et al. Phase II trial for IL-12 plasmid transfection and PD-1 blockade in immunologically quiescent melanoma. Clinical Cancer Research 2020;26 :2827-2837.